Food waste biorefinery: Sustainable strategy for circular bioeconomy - Dahiya, Shikha; Kumar, A. Naresh; Shanthi Sravan, J.; Chatterjee, Sulogna; Sarkar, Omprakash; Mohan, S. Venkata (Bioresource technology, 2018)
•Food waste (unavoidable) is a potential feedstock for bioeconomy.•Food waste biorefinery platform valorizes multiple biobased products sustainably.•Integrating bioprocesses facilitates maximum resource recovery.•Closed loop approach of bioprocesses leads to circular bioeconomy. Enormous quantity of food waste (FW) is becoming a global concern. To address this persistent problem, sustainable interventions with green technologies are essential. FW can be used as potential feedstock in biological processes for the generation of various biobased products along with its remediation. Enabling bioprocesses like acidogenesis, fermentation, methanogenesis, solventogenesis, photosynthesis, oleaginous process, bio-electrogenesis, etc., that yields various products like biofuels, platform chemicals, bioelectricity, biomaterial, biofertilizers, animal feed, etc can be utilized for FW valorisation. Integrating these bioprocesses further enhances the process efficiency and resource recovery sustainably. Adapting biorefinery strategy with integrated approach can lead to the development of circular bioeconomy. The present review highlights the various enabling bioprocesses that can be employed for the generation of energy and various commodity chemicals in an integrated approach addressing sustainability. The waste biorefinery approach for FW needs optimization of the cascade of the individual bioprocesses for the transformation of linear economy to circular bioeconomy.